2014
DOI: 10.2754/avb201483s10s51
|View full text |Cite
|
Sign up to set email alerts
|

The effect of vacuum packaging on physicochemical changes in rainbow trout (Oncorhynchus mykiss) during cold storage

Abstract: The aim of the study was to monitor changes in selected physical (a w water activity, pH values) and chemical (TVBN total volatile basic nitrogen, TMA-N trimethylamine nitrogen, FFA free fatty acids, PV peroxide values, TBA thiobarbituric acid value) properties in the shelf life of rainbow trout (Oncorhynchus mykiss) muscle. A total of 192 trout were examined. Control samples (96 samples) were simply packaged in contact with atmospheric oxygen, while experimental samples (96 samples) were packaged in a commerc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
3
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 18 publications
2
3
0
1
Order By: Relevance
“…With regard to red beet and betaine effects on flesh quality, it has been observed that the inclusion of these ingredients produced a reduction of aw compared to control diet. aw plays an important role on spoilage of fish (Ježek and Buchtová 2014). This is in agreement to the observed with the inclusion of other CHO sources, such as barley (Pinedo et al 2016).…”
Section: : Discussionsupporting
confidence: 89%
“…With regard to red beet and betaine effects on flesh quality, it has been observed that the inclusion of these ingredients produced a reduction of aw compared to control diet. aw plays an important role on spoilage of fish (Ježek and Buchtová 2014). This is in agreement to the observed with the inclusion of other CHO sources, such as barley (Pinedo et al 2016).…”
Section: : Discussionsupporting
confidence: 89%
“…It can be observed that both curves are close in shape and correlate with the coefficient r = 0.85. The onset of the strong TVB-N increase observed on day 11 and later on correlates well with the published data [37,[49][50][51]. Moreover, the value TVB-N at day 7 in Figure 6 (the very onset of bacterial contamination according to the FAO scheme [52]) of 16 ± 2.83 mg/100g agrees very well with the average value that can be deduced from the data in [37,[49][50][51], i.e., 16.25 ± 4.2 mg/100g.…”
Section: Results Of Validation Of Fpmlc Data By Vfa and Tvb-n Methodssupporting
confidence: 90%
“…Moreover,Jezek and Buchtova (2014) suggested TBARS as an indicator of oxidative changes and reported that vacuum packaging resulted in good protection against oxidation in trout muscle.The increase in TVBN value depends on the storage time during the preservation of fish and fish products. The TVBN value determined based on the content of dimethylamine, TMA, ammonia, and other protein derived compounds associated with seafood spoilage(Gokodlu, Ozden, & Erkan, 1998).…”
mentioning
confidence: 99%